2018
DOI: 10.1093/geronb/gby084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Emotion Regulation, Emotional Empathy, and Prosocial Behavior

Abstract: These findings contribute to clarification of mixed previous evidence regarding the experience of emotional empathy in young versus older adulthood. We discuss the importance of considering additional subcomponents of empathy such as emotion regulation, while also accounting for the relevance of the empathy induction to each age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 30 publications
8
58
2
3
Order By: Relevance
“…), and higher magnitude Happy expressions also garnered higher overall ratings. This result is corroborated by previous studies on emotional empathy, which have shown that vivid emotional expressions elicits emotional reactivity in observers (Bailey et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…), and higher magnitude Happy expressions also garnered higher overall ratings. This result is corroborated by previous studies on emotional empathy, which have shown that vivid emotional expressions elicits emotional reactivity in observers (Bailey et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have examined differences in social information processing in older adults (Bailey et al, 2018;Roalf et al, 2011). These studies demonstrate age differences in the evaluation of positive vs. negative.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, most studies have not found lower trait emotional empathy in older adults than younger adults, and the majority of studies have found no age-related differences. Across two studies, Bailey and colleagues found no age-related differences in trait emotional empathy, which included two samples of participants from Australia (9, 29). In the first study by Bailey and colleagues (35), trait emotional empathy was measured by the affective empathy subscale of the Empathy Quotient and assessed age-related differences between younger ( N = 80; 19–25 years; 29% male) and older adults ( N = 49; 65–87 years; 33% male).…”
Section: Aging and Empathy: Psychological Mechanismsmentioning
confidence: 98%
“…Durante estas etapas, las habilidades para el reconocimiento de las emociones aún se encuentran madurando y se asocian a las habilidades para la regulación de las emociones (Thompson, 2011;Zimmer-mann, 1999;Zimmermann y Iwanski, 2014). Más aún, algunos estudios evidenciaron que, en comparación con los adultos más grandes, los adultos emergentes presentaron menores recursos cognitivos para la regulación de las emociones (Yeung, Wong y Lok, 2011) y realizaron menores esfuerzos para ayudar a otra persona a resolver una tarea (Bailey et al, 2018).…”
Section: Discussionunclassified